TRANSFORMASI PERGURUAN TINGGI ISLAM: STRATEGI KEUNGGULAN DAYA SAING MENUJU WORLD CLASS UNIVERSITY - As'ad As'ad (Hijri, 2021)
The argument of this article is that Islamic universities are currently trying to increase competitiveness as an effort to become a world-class university. But in fact Islamic universities are still not optimally preparing for competitiveness against competing universities. This study uses a qualitative method with a multi-case approach. Data were collected by observation and documentation. The research finding is that currently the desire of Islamic universities to become world-class universities is still limited to a vision and has not been implemented properly. Becoming a world-class university requires strong differentiation, especially in the field of research. Researchers suggest that Islamic universities that have a vision of a world-class university to further strengthen the field of research.